Is cryptogenic stroke a tenable diagnosis? The Milpark Hospital patent foramen ovale closure experience - Rapeport, Naomi; Schamroth, Colin; Patel, Nalin (SA Heart Journal, 2017)
Patent foramen ovale (PFO) is increasingly being documented in patients presenting with “cryptogenic” neurological and peripheral ischemic events. Therapeutic options include the use of anti-platelet agents and in some cases non-surgical closure of the defect. In this article we present the Milpark Hospital experience of percutaneous closure of PFO to date. The importance of looking for this defect is highlighted, particularly in patients presenting with recurrent events despite antiplatelet therapy. Whilst routine closure of PFO is not advocated, it should be considered in certain select cases.